Leukoreductive response to the combination of sorafenib and chemotherapy in hyperleukocytosis of FLT3-ITD mutated pediatric AML - Schmidt, Franziska; Erlacher, Miriam; Niemeyer, Charlotte; Reinhardt, Dirk; Klusmann, Jan-Henning (Frontiers in Pediatrics, 2022)
Twelve to 22% of pediatric acute myeloid leukemia (AML) patients present with hyperleukocytosis, which is one of the main risk factors of early death due to its clinical complications: leukostasis, causing pulmonary or central nervous system injuries, tumor lysis syndrome, and disseminated intravascular coagulation. Sorafenib is a multi-kinase inhibitor that blocks the Fms-Related Tyrosine Kinase 3 receptor (FLT3) in AML patients with a FLT3-internal tandem duplication (FLT3-ITD), leading to a reduction of proliferation. Here we report four de novo diagnosed or relapsed pediatric FLT3-ITD–positive AML patients with hyperleukocytosis, which were treated with sorafenib in combination with cytoreductive chemotherapy prior to the start of the induction phase. We observed a fast reduction of white blood cells in peripheral blood and bone marrow. This resulted in a rapid clinical stabilization of the patients. Adverse side effects - such as dermatologic toxicity, elevation of transaminases and hypertension – occurred but were mild and inductive chemotherapy could be started in parallel or subsequently. This implies sorafenib as a treatment option for children with this life-threatening condition.